PEMILU (PEMILIHAN UMUM) DALAM KAJIAN POLITIK ISLAM - ,, Joni Zulhendra (Normative Jurnal Ilmiah Hukum, 2022)
Politics and general elections (elections) are a means or tool for restoring the rights of the ummah to elect leaders of the ummah and elect their representatives who will later speak, express opinions, demand, defend and protect their rights from things that harm them. There is a difference between the elections that are taking place in Indonesia today and what is happening in Islam. The attitude of the ulama towards the election is divided into two groups with different views. The first group, namely those who forbid elections as is currently practiced. According to this group, the current election is not in accordance with sharia. Because the election is not legal or haram, it is not permissible to take or practice the election method in the form that is practiced today.The second group is of the view that the election is justified as it is currently practiced because it is still within the corridor of sharia. This group argues that the election as practiced today is lawful, as long as the election method is in accordance with sharia.